Flying in the face of fear : a fighter pilot's lessons on leading with courage - Campbell, Kim (Air Force Colonel) (Ascent Audio, 2023)
In Flying in the Face of Fear: Lessons on Leading with Courage, former fighter pilot and retired Air Force Colonel Kim Campbell delivers an inspiring and practical discussion of leadership and decision-making. In the book, you'll follow the author's journey through the principles that got her through her twenty-four-year career in the high-stakes and high-risk world of aerial combat. You'll discover lessons and stories that will serve as a resource for you as you lead your students, employees, and others through the challenges of life and work, learning to create a positive impact and make a big difference in the lives of the people who follow you. You'll also find: specific strategies and techniques for leading in situations of extreme stress and risk; methods for female leaders to overcome the challenges of working in male-dominated environments; and ways to act in critical moments by recognizing that being brave and afraid at the same time is both normal and necessary. An essential leadership blueprint for business and military professionals seeking to improve their ability to inspire others to greater achievements, Flying in the Face of Fear will also earn a place in the libraries of young and mid-career professionals looking for mentorship and sound, proven advice.